Investigating the Effect of Trivalent Chromium Cr(III) Contamination on Geotechnical Properties of Clayey Soil - Ali H. Bhatti; Mohammad J. Qadeer; Salman A. Suhail; Usman Pervaiz; Muhammad Qasim; Imtiaz Afzal Khan; Eui-Jong Lee; Sungju Lm; Kang Hoon Lee (Civil Engineering Journal, 2026)
Industrial wastes in the form of chromium, generated by leather industries, commonly contaminate soil, affecting its geotechnical properties. The present study examines the impact of trivalent chromium Cr(III) on the soil’s mechanical, physiochemical, and microstructural properties. The soil and Cr(III) were collected from an industrial area in Sheikhupura, Pakistan, and are mixed in various proportions ranging from 0% to 50% by weight to simulate various contamination levels. A detailed experimental program that included index and strength testing, in addition to physiochemical analysis, was carried out. Modifications in microstructure and mineralogical composition were also examined using Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The results showed an increase in the soil strength characteristics, with maximum dry density (MDD) and cohesion enhanced up to 15% and 12%, respectively, with an addition of Cr(III) up to 20% contamination concentration. Notable reduction in the soil pH was also observed, indicating the acidic impact of Cr(III). Microstructural examination affirmed significant mineralogical rearrangement, with quartz remaining the dominant mineral. The results provided useful insights into the geotechnical implications of Cr(III) contamination in clayey soils and will contribute to improved assessment of the soil behavior in industrially contaminated zones.